Altered Glucose Uptake in Muscle, Visceral Adipose Tissue, and Brain Predict Whole-Body Insulin Resistance and may Contribute to the Development of Type 2 Diabetes: A Combined PET/MR Study - Boersma, Gretha J.; Johansson, Emil; Pereira, Maria J.; Heurling, Kerstin; Skrtic, Stanko; Lau, Joey; Katsogiannos, Petros; Panagiotou, Grigorios; Lubberink, Mark; Kullberg, Joel; Ahlström, Håkan; Eriksson, Jan W. (Hormone and Metabolic Research, 2018)
We assessed glucose uptake in different tissues in type 2 diabetes (T2D), prediabetes, and control subjects to elucidate its impact in the development of whole-body insulin resistance and T2D. Thirteen T2D, 12 prediabetes, and 10 control subjects, matched for age and BMI, underwent OGTT and abdominal subcutaneous adipose tissue (SAT) biopsies. Integrated whole-body 18F-FDG PET and MRI were performed during a hyperinsulinemic euglycemic clamp to asses glucose uptake rate (MRglu) in several tissues. MRglu in skeletal muscle, SAT, visceral adipose tissue (VAT), and liver was significantly reduced in T2D subjects and correlated positively with M-values (r=0.884, r=0.574, r=0.707 and r=0.403, respectively). Brain MRglu was significantly higher in T2D and prediabetes subjects and had a significant inverse correlation with M-values (r=–0.616). Myocardial MRglu did not differ between groups and did not correlate with the M-values. A multivariate model including skeletal muscle, brain and VAT MRglu best predicted the M-values (adjusted r2=0.85). In addition, SAT MRglu correlated with SAT glucose uptake ex vivo (r=0.491). In different stages of the development of T2D, glucose uptake during hyperinsulinemia is elevated in the brain in parallel with an impairment in peripheral organs. Impaired glucose uptake in skeletal muscle and VAT together with elevated glucose uptake in brain were independently associated with whole-body insulin resistance, and these tissue-specific alterations may contribute to T2D development.
Keywords: diabetes mellitus type 2; glucose intolerance; insulin resistance; PET-MRI imaging